The Destruction of Social Capital In Indonesia - Zainuri; Rafael Purtomo S.; Rizal Umami, Mochamad; I Wayan Subagiarta (International Journal of Science, Technology & Management, 2021)
Business failure in the economic system causes various economicactors to potentially become rent-seekers in an imperfect political system. Sugar isan agricultural commodity that, thus far, is a public good that needs governmentregulation. This study aims to determine the social capital of Indonesia's sugarinterest groups and to determine the dominant variable in Indonesia's sugarindustry. Materials and Methods: This research uses a type of explanatory researchthat has a high relationship level because it not only has independent andcomparative values but also serves to explain and predict the relationship with aqualitative approach between variables. Relationship analysis using DecisionExplorer version 3.3 software. Results: analysis of the relationship of and variablein the sugar industry, the more variables involved in the loop, the most importantrelationship between variables in the loop, the most important loop is loop 4consisting of economic rent, the refined sugar market, entrepreneurs in food andbeverage, lobbying, government. Conclusion: It is concluded from the findings ofthis study that the social capital of Indonesia's sugar interest groups consists of 9loops, Almost every variable has a weak strength to social capital and leads todamage.